The impact of the COVID-19 pandemic outbreak on the sustainable development of the Turkish banking sector - Erden, Bahattin; Aslan, Ömer Faruk (Frontiers in Environmental Science, 2022)
This study tries to investigate the development in the banking sector by considering the correlation values before and after March 2020 including the COVID-19 pandemic period in the case of Turkey. However, the full influence of the pandemic will take place in the long term. The number of banks in Turkey, the number of domestic/foreign branches, the number of deposit/participation banks, the volume of the financial sector in gross domestic product (GDP), the number of personnel working in banks, the total number of savings deposits of banks, the total amount of savings deposits of banks, the total number of automatic teller machines (ATMs)/point of sale (POS) owned by the banks, and their relations with the data of the number of establishments are the members of the bank. In Spearman’s correlation, these will be reviewed in the course of correlations. As a result of the analysis, a high level of positive correlation was detected in most of the variables, while an admirable level of positive correlation was determined between the two variables.